The Role of Artificial Intelligence in Optimizing Zakat Distribution in Malaysia: An Analysis of Ethical and Sharia Efficiency - bin Abdul Rahim, Mohd Fazlon (Tunas Institute, 2025)
Ideally, zakat distribution in Malaysia functions as a primary instrument for economic equity and social justice based on maqasid al-shariah values. However, in reality, conventional mechanisms still face various challenges such as targeting inaccuracy, administrative bureaucracy, and the lack of integrated data between muzakki and mustahik. This situation demands innovation capable of addressing efficiency issues while preserving Islamic ethical principles—one of which is through the application of Artificial Intelligence (AI) in zakat management systems. This study aims to examine the role of AI in enhancing the effectiveness of zakat distribution while maintaining efficiency and Shariah compliance. The research employs a qualitative method through literature analysis of Malaysian zakat institution policies, academic articles, and documents on zakat digitalization. The findings reveal that AI can accelerate mustahik classification, optimize transparency in distribution, and reduce the risk of social inequality. Nevertheless, the integration of AI requires continuous ethical oversight to ensure that technology serves not only technical efficiency but also aligns with Islamic values of justice and humanity. The synergy between digital innovation and Shariah ethics is thus essential to building an intelligent and equitable zakat ecosystem.